Depression-Like Responses Induced by Daytime Light Deficiency in the Diurnal Grass Rat (Arvicanthis niloticus) - Leach, Greg (Public Library of Science, 2013)
Seasonal Affective Disorder (SAD) is one of the most common mood disorders with depressive symptoms recurring in winter when there is less sunlight. The fact that light is the most salient factor entraining circadian rhythms leads to the phase-shifting hypothesis, which suggests that the depressive episodes of SAD are caused by misalignments between the circadian rhythms and the habitual sleep times. However, how changes in environmental lighting conditions lead to the fluctuations in mood is largely unknown. The objective of this study is to develop an animal model for some of the features/symptoms of SAD using the diurnal grass rats Arvichantis niloticus and to explore the neural mechanisms underlying the light associated mood changes. Animals were housed in either a 12∶12 hr bright light∶dark (1000lux, BLD) or dim light∶dark (50lux, DLD) condition. The depression-like behaviors were assessed by sweet-taste Saccharin solution preference (SSP) and forced swimming test (FST). Animals in the DLD group showed higher levels of depression-like behaviors compared to those in BLD. The anxiety-like behaviors were assessed in open field and light/dark box test, however no significant differences were observed between the two groups. The involvement of the circadian system on depression-like behaviors was investigated as well. Analysis of locomotor activity revealed no major differences in daily rhythms that could possibly contribute to the depression-like behaviors. To explore the neural substrates associated with the depression-like behaviors, the brain tissues from these animals were analyzed using immunocytochemistry. Attenuated indices of 5-HT signaling were observed in DLD compared to the BLD group. The results lay the groundwork for establishing a novel animal model and a novel experimental paradigm for SAD. The results also provide insights into the neural mechanisms underlying light-dependent mood changes.